Leveraging Social Media Networks' Impact on Technopreneurship - Isa, Khairunesa; Palpanadan, Sarala Thulasi; Saparudin, Intan Farhana; Zainol, Nur Zainatul Nadra; Syahrudin (International Journal of Advanced Science Computing and Engineering, 2023)
Technology has become an integral part of society, substantially contributing to its many facets. With the advent of technology, media entrepreneurship in Malaysia has expanded significantly. The younger generation, specifically Generation Z, relies heavily on social media for communication, information inquiry, and online purchasing and selling. This change has had a significant impact on the Malaysian field of technopreneurship. Therefore, the purpose of this study is to examine the relationship between the factors that influence Generation Z's use of social media for business and their propensity to engage in technopreneurship. This is a quantitative study that uses a questionnaire to collect demographic information, factors influencing Generation Z to use social media for business, and their motivations or aspirations to partake in technopreneurship activities. 280 respondents from Generation Z technopreneurs were selected through random sampling. The software Statistical Package for the Social Sciences (SPSS) was used to perform a descriptive analysis of the obtained data. According to the study's findings, each factor has a significant relationship with the motivation to engage in technopreneurship